Characterization of the textured surfaces under boundary lubrication. (November 2020) - Yue, Hongzhi; Deng, Jianxin; Zhang, Yun; Meng, Ying; Zou, Xueqian
Abstract: The surface textures have been found effective in improving tribological performance of engineering surfaces. However, the current profiling techniques and parameters are inadequate and/or unsuitable to characterize the textured surfaces. Based on the Abbot-Firestone curve, the RMS deviation and three functional indices describing the bearing and fluid retention properties ( S q, S b i, S c i and S v i ) are reformed to characterize the textured surfaces as well as the normal rough surfaces. The algorithms of the parameters are given and their feasibility is discussed. Comparison is made between the newly developed parameters and the former ones. Experiments are conducted to validate the reformed parameters. It is believed that these parameters are more meaningful in describing the textured surfaces and have a guiding significance for texture design under boundary lubrication. Graphical abstract: Image 1 Highlights: New algorithms were developed for the RMS deviation and three functional indices. New parameters were found universal and more meaningful. New parameters were validated by experiments.